2021
DOI: 10.3389/fanim.2021.744207
|View full text |Cite
|
Sign up to set email alerts
|

The Visual, Auditory, and Physical Environment of Livestock Handling Facilities and Its Effect on Ease of Movement of Cattle, Pigs, and Sheep

Abstract: The visual, auditory, and physical environment livestock are handled in will have an effect on the ease of movement through races and corrals that are used for veterinary treatment, loading trucks or at slaughter houses. When livestock refuse to move easily through a handling facility, people are more likely to use electric goads (prods) or other aversive methods to move them forward. This is a major animal welfare concern. Modification of the environment can improve livestock movement and reduce aversive hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Professional and stress-free animal handling is therefore a central aspect in the husbandry of livestock and in the interest of every farmer. It is granted by the construction of a facility that allows gentle and calm handling of the animals (Grandin, 2021), training personnel in adequate handling methods (allowing habituation), and the development and application of suitable treatment protocols when indicated.…”
Section: Implications and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Professional and stress-free animal handling is therefore a central aspect in the husbandry of livestock and in the interest of every farmer. It is granted by the construction of a facility that allows gentle and calm handling of the animals (Grandin, 2021), training personnel in adequate handling methods (allowing habituation), and the development and application of suitable treatment protocols when indicated.…”
Section: Implications and Limitationsmentioning
confidence: 99%
“…It is widely recognized that stressors can support and increase the risk of developing infectious diseases and of prolongation of illness episodes (Kelley, 1980;Steplewski et al, 1985;Cooper, 1999). Therefore, aside from important and well-acknowledged animal welfare concerns, different zootechnical procedures in animal production, inflicting short-term stress due to handling and restraint, may have an influence on animal productivity (Johnson and Vanjonack, 1976;Miranda-de la Lama et al, 2011Marco-Ramell et al, 2016;Grandin, 2021). For these reasons, different protocols to reduce pain and stress in the animal have been developed since studies have shown not only a benefit in this respect, but also in the later animal health status (Ting et al, 2003;Kretschmann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The position of a cow's eyes results in a predominantly monocular visual field, with only a minor central binocular area. This arrangement affords them a broad panoramic vision (Piggins and Phillips, 1996;Rehkämper et al, 2000;Grandin, 2021). Like many herbivores, cows exhibit saccadic eye movements synchronised across both eyes but can differ in amplitude.…”
Section: Vision Capability In Cattle and The Behaviour Related To Vis...mentioning
confidence: 99%
“…The results of the study show that sheep should only be restrained for as long as absolutely necessary. The handling of sheep should be gentle and as stress-free as possible and the environment should be adapted to the needs of the animals (Grandin, 2021). When and whether sedation is necessary for longer procedures should be discussed critically by veterinarians.…”
Section: Stress Response In Sheep With Chronic Pain and In Healthy Sheepmentioning
confidence: 99%